Directional and Frequency Spread of Surface Ocean Waves From SWIM Measurements. Issue 7 (6th July 2021) - Le Merle, Eva; Hauser, Danièle; Peureux, Charles; Aouf, Lotfi; Schippers, Patricia; Dufour, Christophe; Dalphinet, Alice
Abstract: The "China France Oceanography Satellite" (CFOSAT) launched in 2018 now routinely provides directional ocean wave spectra at the global scale. It consists of analyzing the normalized radar cross‐section measured by the near‐nadir pointing Ku‐Band real‐aperture scanning radar SWIM (Surface Waves Investigation and Monitoring). The significant wave height, dominant wavelength and direction are provided as the main parameters, but here, we analyze additional parameters, namely the frequency width of the omni‐directional spectra, the directional spread of the dominant waves, and the related Benjamin‐Feir index. This latter was proposed in the literature to estimate the probability of extreme waves. We discuss the geographical distributions of these parameters, their relation with sea‐state conditions, and their similarities and differences with respect to the same parameters obtained from the MFWAM numerical wave model and buoy data. We find that the SWIM omni‐directional spectra are narrower and more peaked than the model spectra and that these differences are more obvious in the high sea‐state conditions encountered in the Southern Ocean. We find that under the intense conditions of the Southern Ocean, the SWIM directional spread at the peak is the smallest for swell, the largest for young wind seas, and takes intermediate values for mature wind seas. The directional Benjamin‐Feir index is similar for SWIM and MFWAM, but this is mainly due to compensating effects in the parameters contributing to this index. The results indicate that these shape parameters may be used in the future to better describe the wave space‐time evolution. Plain Language Summary: The France Oceanography Satellite CFOSAT was launched in 2018. It routinely provides for all ocean basins detailed information on the ocean waves, namely the distribution of wave height with direction and wavelength (or wave frequency), obtained from radar measurements. In this study, we analyze several parameters which quantify how the energy spreads around the dominant frequency and the dominant wave propagation direction of the waves. Several of these parameters are also combined to estimate an index, which characterizes the probability of occurrence of extreme waves. To our knowledge, it is the first time that such parameters are accessible from space observations at the global scale. In the paper, we discuss the geographical distributions of these parameters, their relation with sea‐state conditions, and their similarities or differences with respect to the same parameters obtained from a numerical wave prediction model and from buoy observations. We find that compared to the satellite observations, the model indicates narrower and more peaked distributions of energy in frequency, and we propose some explanations on this. Overall, the results indicate that these shape parameters from satellite observations may be used in the future to further understand or validate the physical processes impacting the evolution of waves during growth order decay. Key Points: The Surface Waves Investigation and Monitoring (SWIM) ocean wave spectrum is the narrowest and the most peaked for situations with waves close to the fully development stage For the Southern Ocean conditions, SWIM directional spread at the dominant frequency varies according to the wave development stage Compared to the MFWAM model, SWIM shows more narrow and peaked omnidirectional spectra but similar directional spread of the dominant waves